CURRENT EVIDENCE ON THE USE OF MELATONIN FOR PRIMARY INSOMNIA COMPARED TO BENZODIAZEPINES - Viana, Valéria Goulart; Fialho, Daniel Gomes; Furia, Talyta Rodriguez Doratiotto; Duarte, Ramon Brasileiro; Furlan, Felipe Dall Oglio; Ferreira, Caio de Lima; Heidemann e Silva, João Eugênio Henrique; dos Santos, Patrícia Lemos; Costa, André Gustavo Sampaio; Silva, Katiucia Sá; de Paula, Mariáh França Guimarães Meirelles; Gomes, Jackellyne Alves Peres; et al. (Seven Editora, 2025)
Primary insomnia is one of the most prevalent sleep disorders in the adult population, characterized by difficulty in initiating or maintaining sleep, resulting in significant impairments to health, cognitive performance, and quality of life. Benzodiazepines and GABA-A receptor agonists, known as Z-drugs, are widely used in the pharmacological treatment of insomnia; however, their long-term use is associated with tolerance, dependence, and cognitive impairment. Melatonin, an endogenous hormone responsible for regulating the sleep–wake cycle, has been studied as a safe and physiological therapeutic alternative. This study aimed to analyze the most recent scientific evidence on the efficacy and safety of melatonin and its melatonergic agonists compared to benzodiazepines in the treatment of primary insomnia. An integrative literature review was conducted based on studies published between 2015 and 2025 in PubMed, SciELO, ScienceDirect, and Scopus databases. The results demonstrated that melatonin shows moderate efficacy in sleep onset and maintenance, with a superior safety profile and absence of dependence potential, making it a suitable therapeutic option, especially for elderly and polymedicated patients. It is concluded that melatonin represents a promising, effective, and safe pharmacological alternative for the management of primary insomnia, contributing to more rational clinical practices aligned with evidence-based medicine.DOI: https://doi.org/10.56238/sevened2025.037-027